Eugen Fink: Elements for a Heidegger-Critique (1927-1945) (Phenomenology, Humanities and Sciences, 2020)
This paper aims to discuss the points of convergence and divergence between the philosophical position of young Fink and Heidegger’s thought, with the goal not only of providing the basis for properly posing the question of the Heidegger/Fink relationship, but of highlighting Fink’s early independence and philosophical autonomy as well. After a general introduction, the following themes will be discussed: 1. the philosophical prominence of the Weltfrage; 2. ontology and phenomenology; and (more briefly) 3. theory and praxis; 4. being and truth; 5. ethics of authenticity in Being and Time.
Keywords: Fink; Heidegger; Critique; World; Ethics